The Cat in the Hat comes back - Seuss; Edmondson, Adrian (Collins London, 2004)
The Cat in the Hat is back with more mischievous tricks. This time he leaves a big pink ring in the tub and moves it from place to place with the help of his alphabet friends. Contains book and an audio cassette reading with sound effects and wild music. Intended to encourage children to listen to the story while reading along with the book